A decentralized load control architecture for smart energy consumption in small islands. (February 2020) - Croce, D.; Giuliano, F.; Bonomolo, M.; Leone, G.; Musca, R.; Tinnirello, I.
Highlights: Overgrid adoption of a decentralized load control architecture to allow and improve the smart energy retrofit is proposed. The Overgrid Demand Response (DR) architecture is used for managing the residential flexible loads. The estimation of the aggregated power demand without any centralized server is the aim of the DR. Creating a virtual "community" of smart buildings in the small island is another the aim of the DR. The proposed architecture is able to contrast such events and guarantees also a minimum discomfort for the end-users. Abstract: In this paper we propose the adoption of Overgrid, a new decentralized load control architecture, for balancing the energy production variations introduced with the adoption of renewable sources, facilitating and improving the smart energy retrofit. The system is presented and applied for managing the aggregated daily load profile of a community of domestic end-users in the island of Lampedusa, Italy, exploiting the load profiles gathered in a real measurement campaign. The Overgrid Demand Response (DR) architecture is used for managing the residential flexible loads, estimating the aggregated power demand without any centralized server and creating a virtual "community" of smart buildings in the small island. Two different control schemes are applied considering load curtailing and load shifting in presence of significant variations of the electricity production in the island. Our simulation experiments show how the proposed architecture, without any centralized control, is able to contrast such events and, thanks to load shifting actions, guarantees also a minimum discomfort for the end-users, opening the path to substantial smart energy retrofit of small island communities.